How does temperature trigger biofilm adhesion and growth in Candida albicans and two non‐Candida albicans Candida species?. Issue 11 (9th May 2021) - Casagrande Pierantoni, Debora; Corte, Laura; Casadevall, Arturo; Robert, Vincent; Cardinali, Gianluigi; Tascini, Carlo
Abstract: Background: Biofilm formation on biotic and abiotic surfaces is finely regulated by genetic factors but also by oxygen concentration, pH, temperature and other environmental factors, already extensively explored for bacterial biofilms. Much less is known about fungal biofilm, that is considered a virulence factor for Candida pathogenic species among the few fungal species able to grow and survive at high temperatures such as 37°C as well as those induced by fever. The resistance to high temperatures coupled with the ability to form biofilm are threatening factors of these fungal species that could severely impact at an epidemiological level. Objectives: In this framework, we decided to study the thermal tolerance of biofilms formed by three medical relevant species such as Candida albicans and two non‐ Candida albicans Candida species. Methods: Thirty nosocomial strains were investigated for their ability to adhere and grow in proximity and over body temperature (from 31 to 43°C), mimicking different environmental conditions or severe febrile‐like reactions. Results: Candida sessile cells reacted to different temperatures showing a strain‐specific response. It was observed that the attachment and growth respond differently to the temperature and that mechanism of adhesion has different outputs at high temperature than the growth. Conclusions: This strain‐dependent response is probably instrumental to guarantee the best success to cells for the infection, attachment and growth to occur. These observations reinforce the concept of temperature as a major trigger in the evolution of these species especially in this period of increasing environmental temperatures and excessive domestic heating.